Tongue Squamous Cell Carcinoma and Oral Lichen Planus: A Rare Case Report of a Pregnant Woman - David Moretti; Joël Cucherousset; Nadia Benlagha; Ihsène Taïhi (Clinical Case Reports)
ABSTRACT Squamous cell carcinoma (SCC) of oral mucosa is increasingly affecting younger individuals, particularly in the tongue. SCC can develop from disorders like oral lichen planus (OLP). This case highlights the first known instance of OLP and SCC in a pregnant woman, suggesting hormonal changes and HPV as possible risk factors.